To subtract \( \frac{1}{3} \) from \( \frac{11}{18} \), we first need to express both fractions with a common denominator.
The denominators are 18 and 3. The least common multiple of 18 and 3 is 18. So we can leave \( \frac{11}{18} \) as it is, and convert \( \frac{1}{3} \) to an equivalent fraction with a denominator of 18.
To convert \( \frac{1}{3} \):
\[ \frac{1}{3} = \frac{1 \times 6}{3 \times 6} = \frac{6}{18} \]
Now we can subtract the two fractions:
\[ \frac{11}{18} - \frac{6}{18} = \frac{11 - 6}{18} = \frac{5}{18} \]
Thus,
\[ \frac{11}{18} - \frac{1}{3} = \frac{5}{18} \]
The answer is \( \frac{5}{18} \).